Labor-share dynamics: The role of import competition - Charlotte Paulie (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
Does increasing product-market competition from foreign firms affect domestic labor shares? By combining detailed Swedish firm-level data with an instrumental variable design, I show that an increase in import penetration caused by increased global competition results in a decrease in domestic industry-level labor shares. The decrease comes both from a reallocation of firms' market shares and a fall in labor shares at the firm level. The analysis shows that the negative effect of competition on firm-level labor shares is driven by an increase in productivity that is not met by a corresponding increase in compensation to labor. I use these findings to calibrate a heterogeneous-firm model where domestic and foreign firms compete on the domestic product market. The calibrated model predicts that an increase in foreign competition corresponding to a one standard deviation increase in import penetration results in a 1.12 percentage point increase in welfare.
Keywords: E25; L11; F10; 330; Labor Share; Competition; International Trade; Welfare